CHARACTERIZATION OF ADOLESCENT MOTHERS AND THEIR NEWBORNS, IN A SMALL-SIZED CITY, FROM 1995 TO 2009 - Nayara Cristina Alves de Lima; Thaís Regina Ranussi; Mayckel da Silva Barreto; Sonia Silva Marcon (Universidade Federal do Paraná, 2014)
This is a cross-sectional study that aimed to characterize the profile of adolescent mothers, and to compare social and obstetric characteristics, as well as characteristics of the newborns, among a group of early adolescents (10-14 years old) and late adolescents (15-19 years old), in the city of Bandeirantes, Paraná, Brazil, from 1995 to 2009. Information was collected in June 2012, from the DATASUS database. The results evidenced that, in the period of the study, there were 8,364 deliveries, out of which 1,833 (21.9%) were from adolescents - 73 (3.9%) in early ones, and 1,760 (96.1%) in late ones. Associated with pregnancy in early adolescence, there were characteristics like the mother's lower level of schooling, absence of a partner, smaller number of prenatal care visits, and low birth weight. The findings reiterate that worse socio-demographic conditions influence the occurrence and prognosis of adolescent pregnancy, reinforcing the importance health professionals have in the implementation of strategies that decrease its re (occurrence).